Peri-implantitis: etiology, diagnosis and treatment (Research, Society and Development, 2023)
Nowadays, when looking for a prosthetic rehabilitative solution, patients are increasingly concerned with functionality, comfort and aesthetics, and one of the options that meet all these requirements is dental implants, however these require a certain level of care. on the part of patients as well as dental surgeons, to prevent the emergence of peri-implant diseases such as mucositis and its evolved form to peri-implantitis, diseases that resemble periodontal diseases, starting in such a way silent, however, if not treated, they have the potential to lead to rupture of bone integration and loss of implants. Currently peri-implant diseases can receive surgical and non-surgical treatment depending on the level of evolution in which they are found. This work aims to produce a cluster of information about peri-implant diseases covering their etiology, diagnosis and treatment, which can be used as an informational source for members of the dental community. For this purpose, a descriptive narrative literature review was carried out, using articles in Portuguese and English, as a bibliographic base, available in the online databases, PubMED, Lillacs, BVSsalud and Scielo. At the end of this work, it was concluded that although osseointegrated implants are an excellent rehabilitation option, it is extremely important that professionals are constantly looking for new knowledge to improve their success rates, as well as it is of great importance that patients collaborate following the guidelines of the professionals, so that longer treatment longevity is guaranteed.